Representing the unrepresentable: Victor Klemperer's Holocaust diaries - Jerry Schuchalter (Nordisk Judaistik, 1998)
The purpose of this article is to explore how memory is constructed in Victor Klemperer’s diaries. In the diaries, Klemperer describes his fate as well as the fate of other Jews who did not emigrate during the years 1933–1945. The concrete details of everyday life in the Third Reich only serve to highlight the plight of the besieged poet writing at the end of the days, not knowing whether he will complete his masterpiece or whether he will be executed beforehand. In Klemperer’s diaries normality and horror are continually juxtaposed with one another. The holocaust is thus transformed from a small repertoire of horrifying narratives to a seemingly countless number of actions and movements, some conforming to the principal narratives and others, curiously enough, defying the well known narratives of Auschwitz and extermination. These narratives constitute important source material describing the mentality of the Jewish identity in Germany.